Analysis of EEG tracings in frequency and time domain in hepatic encephalopathy - Pascoli, D.; Guérit, J.M.; Montagnese, S.; de Tourtchaninoff, M.; Minelli, T.; Pellegrini, A.; Del Piccolo, F.; Gatta, A.; Amodio, P. (Computer methods and programs in biomedicine, 2006)
Spectral EEG analysis in hepatic encephalopathy (HE) is usually performed disregarding the effect of epoch length, statistical errors and equipment noise. A study on these items was carried out. In addition, spectral analysis and a new analysis, performed in time domain, were compared in the assessment of HE. The EEG tracings of 73 cirrhotic patients with HE were analyzed. Artifact-free periods of about 1 min were selected. Equipment noise was measured by short-circuiting all the electrodes. The equipment noise was notable below 1.5 Hz; the best epoch length was 4 s and the statistical errors were minimal for the band with the highest relative power. Nineteen per cent of the tracings were unstable. The spectral values were found to be related to liver function and to the degree of HE, whereas the relationship with psychometric variables was poor. The indexes computed by time-domain analysis were found to be better related to psychometric findings. We have provided information on the optimisation of spectral EEG analysis and presented a time-domain analysis giving results related to psychometric tests and liver function.